This discussion board is a place to discuss our Daily Challenges and the math and science
related to those challenges. Explanations are more than just a solution — they should
explain the steps and thinking strategies that you used to obtain the solution. Comments
should further the discussion of math and science.
When posting on Brilliant:
Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.
Markdown
Appears as
*italics* or _italics_
italics
**bold** or __bold__
bold
- bulleted - list
bulleted
list
1. numbered 2. list
numbered
list
Note: you must add a full line of space before and after lists for them to show up correctly
# I indented these lines
# 4 spaces, and now they show
# up as a code block.
print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.
print "hello world"
Math
Appears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3
2×3
2^{34}
234
a_{i-1}
ai−1
\frac{2}{3}
32
\sqrt{2}
2
\sum_{i=1}^3
∑i=13
\sin \theta
sinθ
\boxed{123}
123
Comments
1+2x2+2y2now let, y2⟹1+2x2+2y2=1+2⋅2x2−1+2y2=2⋅(x2−1)=1+2⋅2x2−1+22⋅(x2−1)=1+2⋅2x2−1+(2(x2−1))2=(1+2(x2−1))2
Thus the above equation is always a perfect square when,
y2=2⋅(x2−1)
Rewriting we get,
x2−2y2=1
This is similar to the pell equation
which is of the form x2−ny2=1, where n is an integer
if we make the substitution 2y2=2z2, we can reduce it to the form of a pell equation in x,z
now we have x2−2z2=1
we can find the fundamental solution of the pell equation by writing the sequence of convergents (kihi) to the continued
fractions of n .If (x1,z1) is the fundamental solution of the pell equation then x1=hi and z1=ki for some i such that x is minimal
2=1+2+2+2+2+2+⋱11111
we have k1h1=23
(32−2⋅22)=1
we find that (3,2) is the fundamental solution to the given pell equation
Once the fundamental solution is found the general solution (xk,zk) can be calculated by the relation ,
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
1+2x2+2y2now let, y2⟹1+2x2+2y2=1+2⋅2x2−1+2y2=2⋅(x2−1)=1+2⋅2x2−1+22⋅(x2−1)=1+2⋅2x2−1+(2(x2−1))2=(1+2(x2−1))2
Thus the above equation is always a perfect square when,
y2=2⋅(x2−1)
Rewriting we get,
x2−2y2=1
This is similar to the pell equation which is of the form x2−ny2=1, where n is an integer
if we make the substitution 2y2=2z2, we can reduce it to the form of a pell equation in x,z
now we have x2−2z2=1
we can find the fundamental solution of the pell equation by writing the sequence of convergents (kihi) to the continued fractions of n .If (x1,z1) is the fundamental solution of the pell equation then x1=hi and z1=ki for some i such that x is minimal
2=1+2+2+2+2+2+⋱11111
we have k1h1=23
(32−2⋅22)=1
we find that (3,2) is the fundamental solution to the given pell equation
Once the fundamental solution is found the general solution (xk,zk) can be calculated by the relation ,
(xk+zkn)=(x1+z1n)k
in the above case we get,
(xk+zk2)=(3+22)k
similarly we have,
(xk−zk2)=(3−22)k,as (xk+zk2)×(xk−zk2)=1
thus we get,
xk=2(3+22)k+(3−22)kzk=22(3+22)k−(3−22)k
since we assumed ,2y2=2z2
we have y=2z
⟹yk=2zk=2(3+22)k−(3−22)k
Thus for all numbers of the form
(xk,yk)=(2(3+22)k+(3−22)k,2(3+22)k−(3−22)k)
1+2x2+2y2 will be a perfect square
Log in to reply
That is complete brilliance..Mind blowing solution...Just phenomenal..
Post your solution guys